Agenda ambiental na administração pública A3P: estudo da adesão e ação em uma universidade pública - VIEGAS, Socorro de Fátima Souza da Silva (Universidade da Amazônia, 2022)
The paper analyzes the actions of an Institution of Higher Education Federal - IFES in relation to the directives of the Environmental Agenda in Public Administration - A3P, which expresses inclusion of environmental issues in management. In response to pressure, the IFES are adhering to the A3P through adoption of sustainable practices. This is a qualitative study, based on desk research and a questionnaire with the managers of the organization. The results show that the adequacy of the IFES A3P is partial, especially regarding the disposal of waste, the use of natural resources and sustainable procurement. Greater coherence between the policies of A3P and the organization’s actions searched was identifi ed in the actions that show quality of life of the servers in the workplace. Despite the low level of congruence between the actions of IFES and the directives of the A3P, the study shows the importance of A3P as a conditioning factor to building a sustainable organization.